2018
DOI: 10.1007/s00330-018-5329-y
|View full text |Cite
|
Sign up to set email alerts
|

Could IVIM and ADC help in predicting the KRAS status in patients with rectal cancer?

Abstract: • Rectal cancers with different KRAS mutation statuses demonstrated distinctive diffusion/perfusion characteristics. • Max-ADC, Mean-ADC and D values were lower in the KRAS mutant group. • A higher D* value was demonstrated in the KRAS mutant group. • IVIM-DW MRI may potentially help preoperative KRAS mutant status prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…The 75th percentile pixel value of K showed the highest AUC of 0.871 and the sensitivity, specificity, positive predictive value, and negative predictive value were 81.43%, 78.21%, 77.03%, and 82.43%, respectively [31]. Similarly, Xu et al [32] showed that diffusion-weighted MR imaging-derived para-meters can predict KRAS mutation in rectal cancer. They found that the mean apparent diffusion coefficient and D* (pseudo-diffusion coefficient) had moderate diagnostic significance, with respective AUCs of 0.756 and 0.710 [32].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The 75th percentile pixel value of K showed the highest AUC of 0.871 and the sensitivity, specificity, positive predictive value, and negative predictive value were 81.43%, 78.21%, 77.03%, and 82.43%, respectively [31]. Similarly, Xu et al [32] showed that diffusion-weighted MR imaging-derived para-meters can predict KRAS mutation in rectal cancer. They found that the mean apparent diffusion coefficient and D* (pseudo-diffusion coefficient) had moderate diagnostic significance, with respective AUCs of 0.756 and 0.710 [32].…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, Xu et al [32] showed that diffusion-weighted MR imaging-derived para-meters can predict KRAS mutation in rectal cancer. They found that the mean apparent diffusion coefficient and D* (pseudo-diffusion coefficient) had moderate diagnostic significance, with respective AUCs of 0.756 and 0.710 [32]. Yeo et al [33] reported that the perfusion parameters from dynamic contrastenhanced MR imaging were significantly associated with KRAS mutation.…”
Section: Discussionmentioning
confidence: 93%
“…In medical imaging aspects, MSCT, MRI, and 18F-FDG-PET/CT are all important examinations for us to have further insight into the role of KRAS mutation in rectal carcinoma. Positive results have already been seen on MRI [5,12,21] and 18F-FDG-PET/CT [11,19] for predicting KRAS mutation in colorectal carcinoma. However, CT predictors of KRAS mutation in rectal carcinoma had not been described previously.…”
Section: Discussionmentioning
confidence: 92%
“…Kenji Kawada et al [10,20], found 18 F-FDG accumulation into metastatic CRC assessed by SUVmax (the maximum standardized uptake value for the primary tumor) was associated with KRAS status. As for MRI, Yanyan Xu et al [21], found that lower mean-ADC (apparent diffusion coe cient) and higher D* (pseudodiffusion coe cient) value on MRI with KRAS mutation in rectal carcinoma. And the study of YU RI SHIN et al [5], showed that KRAS mutation was associated with N stage, gross tumor pattern, axial length of the tumor, and the ratio of the axial to the longitudinal dimensions of the tumor on MRI.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 All these results indicated that histogram analysis can provide more information regarding intratumoral heterogeneity. Second, compared with previous studies that only focused on the exon 2 (codons 12 and 13) of KRAS, 12,14,33 we also investigated the presence of KRAS mutations on codons 61, 117, and 146, because these mutations have the same tumorigenic effects and can affect the response to anti-EGFR targeted therapy.…”
Section: Discussionmentioning
confidence: 99%